Le genre d’Athéna dans les tragédies athéniennes - Audrey Vasselin (Genre & Histoire)
The following article focuses on the gender of the Greek goddess Athena, which was seen as surprising by the Greeks themselves. She supports the weaving, which refers partly to the weaving of the future bride’s trousseau and to the newlyweds consecrating their belt to Athena during the Apatouria, but the goddess is often depicted as a warrior. The panoply she wears is the ultimate symbol of virility. She is both parthenos and promachos, combining at the same time two opposite facets of Greek society. For some Greeks, as it happens Athenians of the 5th century BC, the division of roles in the private and the public spheres is based on a gendered ideological construction : to the women, domestic work ; to the men, farming works and war. That dichotomy does not apply to Athena.